Coherent anti-Stokes Raman scattering imaging of microcalcifications associated with breast cancer - Petrov, Georgi I. (Analyst, 2020)
Chemical imaging of calcifications was demonstrated in the depth of a tissue. Using long wavelength excitation, broadband coherent anti-Stokes Raman scattering and hierarchical cluster analysis, imaging and chemical analysis were performed 2 mm below the skin level in a model system. Applications to breast cancer diagnostics and imaging are discussed together with the methods to further extend the depth and improve the spatial resolution of chemical imaging.